2002
DOI: 10.1177/0885328202017001597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Fracture Resistance of Six Denture Base Acrylic Resins

Abstract: Fracture strength of denture base resins is of great concern, and many approaches have been used to strengthen acrylic resin dentures. Fracture resistance of six commercially available acrylic resin denture base materials were compared, through impact and transverse strength tests. Three rapid heat-polymerised resins (QC 20, Meliodent and Trevalon), two high-impact strength resins (Trevalon Hi and Lucitone 199) and a strengthened injection-moulded acrylic resin (SR Ivocap plus) were included in the study. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 8 publications
2
36
0
3
Order By: Relevance
“…Since flexural strength of polymers is very sensitive to the testing procedure, such as amount of deflection or specimen dimensions, direct comparison between the results of this study and those of previous reports should be cautious 10) . However, in general the flexural strength and modulus results of the present study are similar with those of previous reports that tested in water bath 10,[33][34][35] , whereas, particularly for IVO and LUC, they are slightly lower than those of other previous reports tested in air or unknown condition 13,20,36,37) . Our results support findings from the earlier report showing that the breaking load and deflection of acrylic resins tested in 37°C water medium were lower than those tested in air 8) .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Since flexural strength of polymers is very sensitive to the testing procedure, such as amount of deflection or specimen dimensions, direct comparison between the results of this study and those of previous reports should be cautious 10) . However, in general the flexural strength and modulus results of the present study are similar with those of previous reports that tested in water bath 10,[33][34][35] , whereas, particularly for IVO and LUC, they are slightly lower than those of other previous reports tested in air or unknown condition 13,20,36,37) . Our results support findings from the earlier report showing that the breaking load and deflection of acrylic resins tested in 37°C water medium were lower than those tested in air 8) .…”
Section: Discussionsupporting
confidence: 90%
“…These results were supported by the same link in literature data 14,33,34,40) . However, this should be interpreted with caution, because other previous studies showed poor correlation in mean FM-FS data of denture base materials 11,13) . However, for PL-FS association, a previous study reported higher positive correlation coefficient (r=0.94) in one denture base resin with relining materials 14) .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations